Peran Perpustakaan Dalam Melestarikan Warisan Budaya dan Sejarah Lokal - Kurniati Kurniati (THE LIGHT : Journal of Librarianship and Information Science, 2023)
Indonesia, as a country rich in cultural heritage, has cultural diversity that stretches from Aceh to Papua. The role of the library is very significant as a form of effort in maintaining and preserving these cultural values. Libraries play an important role as guardians of knowledge, culture and civilization of a nation. This is where various national cultural products are collected, recorded, grouped, preserved, and presented to the community for further development. This aspect becomes a collective contemplation, especially in the context of the problems expressed in the title above. The Unitary State of the Republic of Indonesia, which consists of various islands and stretches from the western tip of Sumatra to the east of Papua, has an area comparable to the area of ??the European continent. Within this framework, the role of the library is very important as a place of preservation for various cultures in Indonesia. Cultural wealth, including in the form of manuscripts, is the creation of the glorious civilization of the Indonesian people in the past. The contents of the values ??and outlook on life contained in these texts need to be maintained because they will be a driving force for the progress of the nation in the current era of globalization. Libraries play a crucial role in realizing efforts to preserve the nation's cultural heritage. One of the ways is by supporting research, study, and dissemination of the noble values ??contained therein. Through this function, the library not only maintains cultural heritage, but also ensures the continuation of these values ??for future generations. Thus, the library plays a role as the vanguard in efforts to preserve cultural values ??and pass them on to the future.